Mitigation of perioperative neurocognitive disorders: A holistic approach - Safavynia, Seyed A.; Goldstein, Peter A.; Evered, Lisbeth A. (Frontiers in Aging Neuroscience, 2022)
William Morton introduced the world to ether anesthesia for use during surgery in the Bullfinch Building of the Massachusetts General Hospital on October 16, 1846. For nearly two centuries, the prevailing wisdom had been that the effects of general anesthetics were rapidly and fully reversible, with no apparent long-term adverse sequelae. Despite occasional concerns of a possible association between surgery and anesthesia with dementia since 1887 (Savage, 1887), our initial belief was robustly punctured following publication in 1998 of the International Study of Post-Operative Cognitive Dysfunction [ISPOCD 1] study by Moller et al. in The Lancet, in which they demonstrated in a prospective fashion that there were in fact persistent adverse effects on neurocognitive function up to 3 months following surgery and that these effects were common. Since publication of that landmark study, significant strides have been made in redefining the terminology describing cognitive dysfunction, identifying those patients most at risk, and establishing the underlying etiology of the condition, particularly with respect to the relative contributions of anesthesia and surgery. In 2018, the International Nomenclature Consensus Working Group proposed new nomenclature to standardize identification of and classify perioperative cognitive changes under the umbrella of perioperative neurocognitive disorders (PND) (Evered et al., 2018a). Since then, the new nomenclature has tried to describe post-surgical cognitive derangements within a unifying framework, and has brought to light the need to standardize methodology in clinical studies and motivate such studies with hypotheses of PND pathogenesis. In this narrative review, we highlight the relevant literature regarding recent key developments in PND identification and management throughout the perioperative period. We provide an overview of the new nomenclature and its implications for interpreting risk factors identified by clinical association studies. We then describe current hypotheses for PND development, using data from clinical association studies and neurophysiologic data where appropriate. Finally, we offer broad clinical guidelines for mitigating PND in the perioperative period, highlighting the role of Brain Enhanced Recovery After Surgery (Brain-ERAS) protocols.